"Shaping Political Landscapes: A Comparative Analysis of Ideological Shifts and Power Structures in 20th Century Democracies" - Ishfaq Ahmad Mir (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
ABSTRACT The 20th century was marked by significant political transformations, including the rise and fall of various ideologies, changes in governance structures, and shifts in global power dynamics. This study seeks to unravel the complexities of these changes, offering insights into the driving forces behind them and their implications for contemporary political thought and practice. It discusses key theories and concepts in political science, offering a solid foundation for the comparative analysis that follows. By examining a diverse set of case studies representing different regions and historical contexts, this research aims to provide a holistic perspective on the subject matter. It underscores the importance of historical context and regional variation in understanding the political evolution of these nations. The paper concludes with recommendations for policymakers and scholars to consider in the context of contemporary political challenges. It also suggests potential avenues for future research, as the subject matter continues to evolve in the 21st century. Through this comprehensive analysis, our research contributes to a deeper understanding of the dynamics that have shaped political landscapes in democratic nations and their enduring impact on the present day.